Design and analysis of ultra-broadband distributed power amplifiers for multi-platform communications - Thein, Than Tun (2014)
The growth in wireless communication, the evolution of applications in smart mobile devices, the elimination of cord clutter from devices and different spectrum allocations around the world are calling for integration of multiple communication platforms in a single device. Implementing multiple arrow-band amplifier chips with corresponding matching networks and biasing circuitry to fulfill the requirements will be a complicated way. This indicates a need for ultra-roadband amplifier, which can operate over a wide range of frequency to eliminate various individual narrowband